2012
DOI: 10.1111/j.1651-2227.2012.02728.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use in infants in the first year of life in five European countries

Abstract: AbstractsOther managements were similar in all groups. Stool weight(g) and duration of diarrhea were the primary outcomes. Results There was a trend in stool weight reduction in the groups receiving L-isoleucine and the reduction was significant on day 2 (mean ± SD, L-isoleucine vs. vit D vs. L -isoleucine + vit D vs. control, 276±228 vs. 386±302 vs. 301± 181 vs. 447± 325, p=0.039) and day3 (176±157 vs. 321±273 vs. 276±169 vs. 341±292, p=0.045). The duration of diarrhea was similar in all groups. Conclusion L-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 31 publications
5
33
1
1
Order By: Relevance
“…Although the halving of antibiotic prescriptions in the TC group was intriguing, we could not confirm this finding by review of mothers' responses to weekly surveys regarding antibiotic use. Half of babies were reported by their mother to have received antibiotics prior to their first birthday, a finding comparable to other studies [25]. Mothers, however, were often unclear as to what medicines were antibiotics: when a random subset of 60 episodes was investigated to confirm their reported antibiotic use, 37% of "antibiotics" were found to be nonantibiotic medications, primarily analgesics (acetaminophen (55%), ibuprofen (5%)) (unpublished data).…”
Section: Discussionsupporting
confidence: 67%
“…Although the halving of antibiotic prescriptions in the TC group was intriguing, we could not confirm this finding by review of mothers' responses to weekly surveys regarding antibiotic use. Half of babies were reported by their mother to have received antibiotics prior to their first birthday, a finding comparable to other studies [25]. Mothers, however, were often unclear as to what medicines were antibiotics: when a random subset of 60 episodes was investigated to confirm their reported antibiotic use, 37% of "antibiotics" were found to be nonantibiotic medications, primarily analgesics (acetaminophen (55%), ibuprofen (5%)) (unpublished data).…”
Section: Discussionsupporting
confidence: 67%
“…When an ARI‐related medical consultation occurred in our cohort, almost half received an antibiotic, more likely for AOM than for other URTIs, so that by the end of the study more than half the cohort had received an antibiotic on at least one occasion. This degree of antibiotic exposure is comparable with other Australian studies and within the broad range of prescribing found within Europe, the United Kingdom, and in the United States of America . A European study observed that while the frequency of infection episodes did not differ between countries, antibiotic prescribing habits were determined by other factors, such as physician attitudes and socio‐economic factors .…”
Section: Discussionmentioning
confidence: 99%
“…This degree of antibiotic exposure is comparable with other Australian studies and within the broad range of prescribing found within Europe, the United Kingdom, and in the United States of America . A European study observed that while the frequency of infection episodes did not differ between countries, antibiotic prescribing habits were determined by other factors, such as physician attitudes and socio‐economic factors . This was highlighted by a recent cross‐sectional survey of common ARI management in young children in Australian family practice .…”
Section: Discussionmentioning
confidence: 99%
“…15 The antibiotic prescription rate varied between countries, ranging from 0.2 to 1.3 prescriptions per infant per year. 16 Antibiotics may have an influence on the prevalence of allergic diseases through two pathways: antibiotics may remove some protective effect against allergies and the antibiotic effect on the commensal bowel may alter gut flora in atopic subjects. 17e20 Therefore, antibiotics use in early life has a higher proportion, and reducing antibiotics use during early life is a feasible method to prevent from AD.…”
Section: Discussionmentioning
confidence: 99%